Observation and modelling of stimulated Raman scattering driven by an optically smoothed laser beam in experimental conditions relevant for shock ignition. (18th October 2021) - Cristoforetti, G.; Hüller, S.; Koester, P.; Antonelli, L.; Atzeni, S.; Baffigi, F.; Batani, D.; Baird, C.; Booth, N.; Galimberti, M.; Glize, K.; Héron, A.; et al.
Abstract: We report results and modelling of an experiment performed at the Target Area West Vulcan laser facility, aimed at investigating laser–plasma interaction in conditions that are of interest for the shock ignition scheme in inertial confinement fusion (ICF), that is, laser intensity higher than ${10}^{16}$ $W/{cm}^2$ impinging on a hot ( $T>1$ keV), inhomogeneous and long scalelength pre-formed plasma. Measurements show a significant stimulated Raman scattering (SRS) backscattering ( $\sim 4%{-}20%$ of laser energy) driven at low plasma densities and no signatures of two-plasmon decay (TPD)/SRS driven at the quarter critical density region. Results are satisfactorily reproduced by an analytical model accounting for the convective SRS growth in independent laser speckles, in conditions where the reflectivity is dominated by the contribution from the most intense speckles, where SRS becomes saturated. Analytical and kinetic simulations well reproduce the onset of SRS at low plasma densities in a regime strongly affected by non-linear Landau damping and by filamentation of the most intense laser speckles. The absence of TPD/SRS at higher densities is explained by pump depletion and plasma smoothing driven by filamentation. The prevalence of laser coupling in the low-density profile justifies the low temperature measured for hot electrons ( $7\!{-}\!12$ keV), which is well reproduced by numerical simulations.